Porcine-induced pluripotent stem cell-derived osteoblast-like cells ameliorate trabecular bone mass of osteoporotic rats. (26th September 2018) - Liao, Yu-Jing; Tang, Pin-Chi; Lin, Chih-Hsun; Chen, Lih-Ren; Yang, Jenn-Rong
Aim: We created rat models of osteoporosis and verified a novel idea to recover bone mass via local cell transplantation.Materials & methods: The rats were treated with ovariectomy, 0.1% calcium diet or 3 mg/kg body weight/day of prednisolone and porcine-induced pluripotent stem cell (piPSC)-derived osteoblast-like cells were transplanted into the medullary cavity of the left femurs.Results: The piPSC-derived osteoblast-like cells exerted therapeutic potential on prednisolone treatment group, which confirmed by improvements in trabecular bone volume (15.93 ± 2.20%), bone surface/volume ratio (27.82 ± 1.40 1/mm), thickness (1.40 ± 0.01 mm), separation (0.99 ± 0.10 mm), number (1.13 ± 0.13 1/mm) and total porosity (84.06 ± 2.20%).Conclusion: These results first uncovered therapeutic potential of xenotransplantation with piPSCs for glucocorticoid-induced osteoporosis treatment in the rat models.